A study on investment strategies applied in PNB: a case study for ASNB unit trust / Nordayana Sri Ridzoan - Ridzoan, Nordayana Sri (Faculty of Business and Management, 2009)
The study provides an analysis regarding the investment strategies applied by PNB towards the ASNB unit trust product in order to ensure the attractiveness of their unitrust products. The main purposes of this study are to identify the investment strategy applied by Amanah Saham Nasional Berhad in allocating all the pooled funds to ensure positive return for the investment and provide general guidance to fund manager and investor on how to manage a portfolio or investments wisely. The data from this study was collected from the secondary data which is including internal data collected from PNB own websites, PNB News, and PNB library books and also from e-Journal, Books and magazines. The findings shown that PNB was implementing most of the investment strategies same as the theory view and it leads PNB unit trust products to be the best in the market and most attractive towards the investors. It’s important to maintain good perceptions of PNB among investor. PNB should implement some of these recommendations in order to tighten the current strategies. PNB also recommended implementing the new strategies of investment to be the most outstanding organization in this industry with the best performance of the funds in the market. It can be done by minimizing the investment costs for variable price scheme and continue implementing the strategies of asset allocation and taking commodities as another alternative asset class.